Developing organizations’ dynamic capabilities and employee mental health in the face of heightened geopolitical tensions, polarized societies and grand societal challenges - Cooke, Fang Lee; Dickmann, Michael; Parry, Emma (Taylor & Francis, 2024)
The year 2023 witnessed intensified geopolitical tensions, military conflicts, and international economic sanctions, with heightened risks and uncertainties for businesses, especially multinational enterprises. In this editorial for 2024, we focus on two phenomena—international sanction and mental health—as critical issues for human resource management research and practice. These two issues are closely related to the United Nations Sustainable Development Goals (Goal 3: Good health and wellbeing and Goal 16: Peace, justice and strong institutions). We draw on dynamic capability theory to illustrate how organizations can develop corporate capabilities to survive and thrive in a volatile global business environment. We suggest sets of research questions to inform policy decisions and practice. We also outline practical implications for human resource professionals.
Keywords: Dynamic capability; geopolitics; international HRM; international sanction; mental health; sustainable development goals